Pengembangan Model Pembelajaran Imajinatif dalam Keterampilan Mengarang pada Siswa SMP Dwiguna Depok - Rahmawati Rahmawati (Universitas Indraprasta PGRI Jakarta, 2017)
Indonesian Language Learning at Junior High School is performed to improve students' ability to communicate with good and correct Indonesian language, both oral and written, and to foster students’ appreciation for Indonesian literary works. The purpose of this study is to describe the improvement of writing skill of students of Dwiguna Depok Junior High School. It is a classroom action research using a two-cycle action model. The subject of the research is Dwiguna junior high school students. Data are obtained from the main instrument, namely research supported by supporting instruments such as observation, interviews, documentation, and field notes. The results show that the writing activity using imaginative learning model has increased, with the students being creative with imagination without any limitations. It is seen from the analysis results showing that the students’ writing skill has improved, meaning this learning model can be used as an alternative to Indonesian Language learning in the classroom.